Making Connections: A Metacognitive Teaching Strategy in Enhancing Students’ Reading Comprehension - Louise Mariz Antoinette G. Nobles; Ruth Ortega-Dela Cruz (Universitas Sembilanbelas November Kolaka, 2020)
Reading comprehension skill is crucial for success beyond academic endeavor. However, even academic success can never be possible when a student does not understand the importance of developing good reading comprehension. Using one-group pretest–posttest research design, the study explored the effect of making connections as a metacognitive teaching strategy to enhance the students’ reading comprehension. Purposively selected college students were given assessments and intervention. Based on the data gathered from the pretest and posttest, findings revealed that application of metacognitive teaching strategy, making connections has a positive effect on enhancing the students’ level of reading comprehension as indicated by an increase from average to very high level. The six levels of reading comprehension which were the literal, inferential, appreciative, critique, and evaluative also showed improvement. Results of the Metacognitive Awareness Reading Strategies Inventory (MARSI) indicated that students were unconsciously using Global reading, Problem-solving, and Support reading strategies. Focus group discussion revealed factors that affect the reading comprehension such as interest, teaching styles, and language. The study suggested the important role that educators play in maximizing the benefits of making connections and making use of any other metacognitive strategy towards developing higher level of comprehension leading to academic success.